PENGARUH KEPEMIMPINAN, PELATIHAN DAN KOMPETENSI TERHADAP KINERJA PERSONEL DIT BINMAS POLDA METRO JAYA - Hariyanto, Rachmad; Djati, S. Pantja (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This study aims to determine the influence of leadership, training and competence on the performance of personnel at the Directorate Binmas of Polda Metro Jaya. The research design used was quantitative and descriptive. Research population of all personnel of Directorate Binmas of Polda Metro Jaya. Non-probability sampling technique with survey sample, so found 80 respondents as sample. Data testing techniques include instrument test and classical assumption test. Methods of multiple linear regression analysis, t test, F test, coefficient of determination test (R2) and inter-dimensional correlation analysis with the help of SPSS 22.0 for windows program. The results showed that leadership, training and competence have a significant positive effect simultaneously on the performance of personnel at the Directorate Binmas of Polda Metro Jaya. Partially, leadership has a significant positive effect on performance, training has no effect on performance and competence have positive and significant effect to performance. Further research is suggested to add other variables that affect the performance that has not been used with different objects or populations such as leadership style and work discipline